The Healing Encounters and Attitudes Lists (HEAL): Psychometric Properties of a German Version (HEAL-D) in Comparison With the Original HEAL - Gerger, Heike; Buergler, Sarah; Sezer, Dilan; Grethler, Marc; Gaab, Jens; Locher, Cosima (Frontiers in Psychiatry, 2020)
Introduction: Over the last years, the interest in understanding health improvements that occur due to non-specific treatment effects, rather than in response to the specific active treatment ingredients, increased. Nevertheless, investigations on patients’ idiosyncratic perspectives on the non-specific aspects of the healing encounter or of the treatment itself that contribute to placebo effects are still rare. The Healing Encounters and Attitudes Lists (HEAL) offer a unique and parsimonious set of instruments to measure patients’ views on a variety of non-specific aspects of the caring encounter. The HEAL items can be administered as computerized adaptive tests or short forms that assess the patient-provider connection, the healthcare environment, treatment expectancy, positive outlook, spirituality, as well as attitudes towards complementary and alternative medicine. So far, no German version of the HEAL exists. Methods: The original 168 HEAL items were translated into German (HEAL-D) applying a translation-back-translation procedure. We examined the psychometric properties of HEAL-D in a sample of 165 participants who reported at least one healthcare visit during the last year. Results: The German short forms of HEAL (HEAL-D-SF) showed good internal consistency and test-retest reliability. The factor structure observed in the English original items showed low to moderate model fit in our sample. Discussion: The development of a German version of HEAL in addition to the original English items offers new possibilities for investigating patients’ idiosyncratic perspectives on the non-specific aspects of treatments across language borders. We will close with presenting possible clinical application as well as promising and relevant future research directions using HEAL-D-SF, including for instance large-scale, cross-national investigations.